2022
DOI: 10.1108/k-04-2022-0487
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamic neural network toolbox design for identification, estimation and control

Abstract: PurposeThere are common problems in the identification of uncertain nonlinear systems, nonparametric approximation, state estimation, and automatic control. Dynamic neural network (DNN) approximation can simplify the development of all the aforementioned problems in either continuous or discrete systems. A DNN is represented by a system of differential or recurrent equations defined in the space of vector activation functions with weights and offsets that are functionally associated with the input data.Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Another level of standardisation is proposed by Chairez et al . (2023) in the field of AI modelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another level of standardisation is proposed by Chairez et al . (2023) in the field of AI modelling.…”
Section: Discussionmentioning
confidence: 99%
“…Another level of standardisation is proposed by Chairez et al (2023) in the field of AI modelling. The authors propose a version of the DNN toolbox that can be used to identify the dynamics of the black box and restore the laws underlying the system using known inputs and outputs, featuring the possibility of developing an algorithmic semi-automatic selection of activation function parameters based on optimisation problem solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Since MCM is based on linearization, it requires linearization when applied to nonlinear systems, which could result in significant residual error [23][24][25]. Iterative learning control (ILC) is adopted in industries to reduce dependencies on models, which is applicable for systems with repetitive movements [26][27]. For a wafer scanner, 6 iterations could reduce the tracking error to an accuracy of 100nm level through parameters update [26].…”
Section: Introductionmentioning
confidence: 99%
“…The advancement in computing and artificial intelligence enables extensive computation, thus supporting more complex strategies [19]. Numerous experimental studies have demonstrated the effectiveness of ICM in handling uncertainty and complexity [27,29]. Neural network control (NNC) is a typical example of ICM, which could adapt and compensate for non-linear errors very well.…”
Section: Introductionmentioning
confidence: 99%